Same-day carotid artery stenting and aortic valve surgery- less invasive treatment for high risk patients - Micovic, Slobodan; Tabaković, Zoran; Soldatovic, Ivan; Vukovic, Petar; Milacic, Petar; Petrovic, Ivana; Matkovic, Milos; Grujic, Stefan; Zivkovic, Igor (Medical Research, 2024)
Introduction: The etiology of aortic valve stenosis (AS) is multifactorial; hypertension, hyperlipidemia, and diabetes mellitus are the most common risk factors for development of the disease. The same factors increase the incidence of atherosclerosis in the peripheral arterial vessels. Hemodynamic disturbance in both diseases increases the risk of cerebrovascular symptomatology. Due to the overlapping of the symptoms in patients with concomitant aortic valve stenosis and carotid artery disease, indication for treatment is not always straightforward.. There are different strategies for treatment; same-day or simultaneous surgery, staged procedure, transcatheter technique, or medical treatment. Aim: The aim of our study is to observe the feasibility and safety of same-day SAVR and CAS in patients with concomitant severe aortic valve and carotid artery stenosis. Material and methods: A prospective non-randomized study performed from August 2015 to August 2023 included thirty-four patients who underwent same-day SAVR (simple or in combination with other cardiac surgery procedures) and CAS intervention.Results: The study included 34 patients with concomitant carotid and aortic disease. The majority of patients had SAVR with CABG procedure. In total, MACCE was reported in 3 patients.Conclusion: The guidelines for treatment strategy are unclear due to a lack of studies about this subject. Surgical aortic valve replacement (SAVR) and carotid artery endarterectomy (CEA) done simultaneously, can yield favorable results but could be excessively invasive for high-risk patients. In these cases, surgical aortic valve replacement and carotid artery stenting (CAS) are feasible, less invasive option.
Keywords: Carotid artery stenting, aortic valve stenosis, surgical aortic valve replacement